2001
DOI: 10.1177/000841740106800205
|View full text |Cite
|
Sign up to set email alerts
|

Cultural Competence in New Zealand and Canada: Occupational Therapy Students' Reflections on Class and Fieldwork Curriculum

Abstract: The first year of a twin study undertaken between two occupational therapy programs in Canada and New Zealand is described. The primary aims of the study were to illuminate the lived experiences of students as they learn about cultural difference and had contact with clients of differing cultural backgrounds to themselves during fieldwork placements. While there are similarities between educational programs and the demographic profiles of the two cohorts of students, there are curricular differences primarily … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 14 publications
1
28
0
Order By: Relevance
“…Many authors have described and prescribed cultural competence pedagogy specific to different professional disciplines such as medicine 4 , nursing, [8][9][10][11] social work, 12-14 psychology, 15 and occupational and physical therapy. [16][17][18] Others have suggested that cultural competence education is particularly salient for multidisciplinary teams. [19][20][21] Literature specific to development of cultural competence among hospice providers is beginning to appear.…”
Section: Approaches To Cultural Competence Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…Many authors have described and prescribed cultural competence pedagogy specific to different professional disciplines such as medicine 4 , nursing, [8][9][10][11] social work, 12-14 psychology, 15 and occupational and physical therapy. [16][17][18] Others have suggested that cultural competence education is particularly salient for multidisciplinary teams. [19][20][21] Literature specific to development of cultural competence among hospice providers is beginning to appear.…”
Section: Approaches To Cultural Competence Educationmentioning
confidence: 99%
“…Within these moreengaged interventions there is also a range, from special clinical experiences designed to take advantage of different communities close to home 29 to those that provide experiences in international travel and living abroad. 16,17,30 In theory, the more active engagement the teaching method requires, the more opportunities there are for knowledge, awareness, affective, and skill-oriented learning and the more occasions to use inquiry-centered strategies.…”
Section: Approaches To Cultural Competence Educationmentioning
confidence: 99%
“…Fieldwork education is a large part of the occupational therapy curriculum. It is the foundation on which students build their education and careers; it enables students to become competent therapists in various areas of practice and facilitates the development of effective practice habits (Bonello, 2001;Crowe & Mackenzie, 2001;Forwell, Whiteford & Dyck, 2001;Pope-Davis, Prieto, Whitaker & Pope-Davis, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…In Whiteford and Wright-St. Clair's (2002) longitudinal phenomenological study, students identified hands-on experiences with diverse populations as the most effective cross-cultural learning approach. Training approaches using ethnographic interviewing (Wongsaroj, 2000;Yuen & Yau, 1999), field immersion in international contexts (Ekelman, Dal Bello-Hass, Bazyk, & Bazyk, 2003), or the use of case stories (Forwell, Whiteford, & Dyck, 2001) have also been reported as effective training methods for limited samples.…”
mentioning
confidence: 99%